Lenn E. Goodman : Judaism, humanity, and nature - Tirosh-Samuelson, Hava, 1950-; Hughes, Aaron W., 1968- (Library of Contemporary Jewish Philosophers, 2015)
Lenn E. Goodman is Professor of Philosophy and Andrew W. Mellon Professor in the Humanities at Vanderbilt University in Nashville, Tennessee. Trained in medieval Arabic and Hebrew philosophy and intellectual history, his prolific scholarship has covered the entire history of philosophy from antiquity to the present with a focus on medieval Jewish philosophy. A synthetic philosopher, Goodman has drawn on Jewish religious sources (e.g., Bible, Midrash, Mishnah, and Talmud) as well as philosophic sources (Jewish, Muslim, and Christian), in an attempt to construct his own distinctive theory about the natural basis of morality and justice. Taking his cue from medieval Jewish philosophers such as Maimonides, Goodman offers a new theoretical framework for Jewish communal life that is attentive to contemporary philosophy and science.